2021
DOI: 10.1111/febs.16146
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear organoids: progress and outlook, with a focus on the vascularization

Abstract: The inner ear is a complex organ that encodes sound, motion and orientation in space. Given the complexity of the inner ear, it is not surprising that treatments are relatively limited despite the fact that, in 2015, hearing loss was the fourth leading cause of years lived with disability (YLDs) worldwide. Inner ear organoid models are a promising tool to advance the study of multiple aspects of the inner ear to aid the development of new treatments and validate drug-based therapies. The blood supply of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
(184 reference statements)
0
5
0
Order By: Relevance
“…The anatomical location of the auditory organ of the inner ear is deeply buried in the temporal side of the head, which makes it impossible to pursue the conventional treatment through surgical treatment, drug delivery, and tissue engineering technology 43,44 . Recently, kinds of organoid models are promising tools to advance the study of regenerative medicine, which validates the rapid development of new treatments of drug or gene‐based therapies 20 . Up to now, the overwhelming majority of inner ear organoids derived from the stem cells, especially PSCs 45 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The anatomical location of the auditory organ of the inner ear is deeply buried in the temporal side of the head, which makes it impossible to pursue the conventional treatment through surgical treatment, drug delivery, and tissue engineering technology 43,44 . Recently, kinds of organoid models are promising tools to advance the study of regenerative medicine, which validates the rapid development of new treatments of drug or gene‐based therapies 20 . Up to now, the overwhelming majority of inner ear organoids derived from the stem cells, especially PSCs 45 .…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Recently, kinds of organoid models are promising tools to advance the study of regenerative medicine, which validates the rapid development of new treatments of drug or gene-based therapies. 20 Up to now, the overwhelming majority of inner ear organoids derived from the stem cells, especially PSCs. 45 However, these stem cell-based organoids unable to structurally and functionally mimic the organ of Corti microenvironment in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite several research trials on the development of the inner ear, cellular models of the inner ear have not gained popularity as drug discovery platforms. Over the past decade, studies have focused on optimizing and improving the development of inner ear organoids (IEOs). These studies have demonstrated that embryonic-stem-cell (ESC)- and induced pluripotent stem-cell-based IEOs can possess sensory hair cells, supporting cells, and neurons based on the definitive ectoderm in embryonic development. …”
mentioning
confidence: 99%